Ontologies of Community in Postmodernist American Fiction - Sutton, Malcolm (Université d'Ottawa / University of Ottawa, 2012)
Using a number of structurally innovative novels from the 1970s, 1980s and 1990s as a basis for study, this dissertation examines the representation of communities in postmodernist American fiction. While novels have often been critically studied from the standpoint of the individual and society, here the often neglected category of community is put under scrutiny. Yet rather than considering it from a sociological point of view, which can potentially favour historical, economic or political grounds for community, this study focuses on the ontological binds formed between individual and community. On one level this study connects formal qualities of postmodernist novels to a representation of community – especially literary conventions from the past that are foregrounded in the present texts. On another level it interrogates the limits of the individual in relation to others – how we emerge from others, how we are discrete from others, how much we can actually share with others, at what cost we stay or break with the others who have most influenced us. The primary novels studied here, each of which is deeply invested in the community as a locus for ontological interrogation, are Robert Coover’s "Gerald’s Party" (1985) and "John’s Wife" (1996), Gilbert Sorrentino’s "Crystal Vision" (1981) and "Odd Number" (1985), Harry Mathews’s "Cigarettes" (1987), Joseph McElroy’s "Women and Men" (1987), and Toni Morrison’s "Paradise" (1997). Despite their varied representations of and attitudes toward the individual in community, these texts share a common spectre of American Romanticism that inflects how we read the possibility of community in the postmodernist period.
Keywords: community; American literature; American fiction; Robert Coover; Harry Mathews; Joseph McElroy; Toni Morrison; ontology; postmodernism; Gilbert Sorrentino